Predicting Urban Green Infrastructures of Ecosystem Services in Tehran Metropolitan Area Sprawl with Landsat Satellite time Series Data - Nasr, Tahereh; Jafarpour Ghalehteimouri, Kamran; Khedmatzadeh, Ali; Najaf Mousavi, Mir; Rajabi, Azita (Journal of Architectural/Planning Research and Studies (JARS), 2024)
Urban green infrastructures play a crucial role in providing ecosystem services in metropolitan areas. However, the rapid urbanization and destruction of these infrastructures have become major concerns in the Tehran Metropolitan Region (TMR). This study focuses on analyzing the changes in Land Use and Land Cover (LULC) to highlight the significance of urban ecosystem services. The research utilized free Landsat time-series data from 2000, 2010, and 2020 to create a TMR development dataset. The study employed cellular automata and Markov chains to demonstrate the changes in LULC and the decline of urban green infrastructures in TMR. Six validated LULC classes were selected, including built up, garden, rainfed, soil and mountain, water, and cultivation. The data indicated that TMR’s agricultural development and urban green infrastructures have increased by 21% since 2000, reaching 45% in 2020, and are expected to grow by 43% of the TMR’s total LULC until 2040. The study highlights the potential risks of overusing lands for green infrastructure development, which have been as results of human activities by rapid urbanization, industrialization, and population growth. Furthermore, the growth of green infrastructure at the provincial level does not fully support TMR’s ecological capabilities. This study emphasizes the need for effective urban planning policies to ensure the sustainable development of urban green infrastructures and ecosystem services in metropolitan areas.